Short-Term Outcomes After Multisystem Inflammatory Syndrome in Children Treatment. (19th November 2020) - Clouser, Katharine N; Gadhavi, Jasmine; Bhavsar, Sejal M; Lewis, Rachel; Ballance, Cathleen; Michalak, Zuzanna; Baer, Aryeh; Kriegel, Marni; Pall, Harpreet; Piwoz, Julia; Slavin, Kevin; Siegel, Mark E; et al.
Abstract: This is a retrospective chart review of 20 patients treated with a consensus-driven treatment algorithm in multisystem inflammatory syndrome in children patients across a wide clinical spectrum. Their treatments and clinical status are described as well as their favorable return to functional baseline by 30 days post presentation.